2019
DOI: 10.3390/nu11071677
|View full text |Cite
|
Sign up to set email alerts
|

Linseed Components Are More Effective Than Whole Linseed in Reversing Diet-Induced Metabolic Syndrome in Rats

Abstract: Linseed is a dietary source of plant-based ω–3 fatty acids along with fiber as well as lignans including secoisolariciresinol diglucoside (SDG). We investigated the reversal of signs of metabolic syndrome following addition of whole linseed (5%), defatted linseed (3%), or SDG (0.03%) to either a high-carbohydrate, high-fat or corn starch diet for rats for the final eight weeks of a 16–week protocol. All interventions reduced plasma insulin, systolic blood pressure, inflammatory cell infiltration in heart, vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…We are very grateful to these experts who have agreed to contribute to this issue [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Original papers that are relevant to our theme are also included [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: This Issuementioning
confidence: 99%
“…We are very grateful to these experts who have agreed to contribute to this issue [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Original papers that are relevant to our theme are also included [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: This Issuementioning
confidence: 99%
“…The majority of the families exhibited high fiber content, where 11 families registered the highest values (varies between 23% and 27%) compared to the overall average of 11.83%. The high fiber content makes these families suitable to promote heart health by reducing total cholesterol level (Brink & Achigan‐Dako, 2016; Parikh, Maddaford, et al, 2018, Parikh, Netticadan, & Pierce, 2018; Shafie et al, 2019; Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, linseed has been previously used in human trials and demonstrated some beneficial effects on human health [ 28 ]. Therefore, besides the beneficial effects of n-3 PUFA, linseed, a matrix with fatty acids, fibers, lignans, and other bioactive components, may have a therapeutic effect on human health and CD prevention [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%